Transposable elements in cancer as a by-product of stress-induced evolvability - Mourier, Tobias; Nielsen, Lars P.; Hansen, Anders J.; Willerslev, Eske (Frontiers in Genetics, 2014)
Transposable elements (TEs) are ubiquitous in eukaryotic genomes. Barbara McClintock's famous notion of TEs acting as controlling elements modifying the genetic response of an organism upon exposure to stressful environments has since been solidly supported in a series of model organisms. This requires the TE activity response to possess an element of specificity and be targeted towards certain parts of the genome. We propose that a similar TE response is present in human cells, and that this stress response may drive the onset of human cancers. As such, TE-driven cancers may be viewed as an evolutionary by-product of organisms' abilities to genetically adapt to environmental stress.